WHICH IS MORE TRUSTWORTHY: GOOGLE OR DOCTOR? A RECEPTION ANALYSIS OF MEDIA AS HEALTH EDUCATOR - Yoanita, Desi; Lesmana, Fanny; Primasanti, Kartika B. (Scriptura, 2015)
As media develops as a primary source of health information, two questions remains: How people receive online media as a source of health education? and what group of people will tend to use online media intensively than others? Although government has provided various ways to fulfill people’s health needs has been considered a development on health policy in Indonesia, examining contemporary situation and current online media development reveals a need for exploring how people receive online media as health educator. This research study depicted how people from a certain background receive online media as health educator. Using a reception analysis, the research study has conducted through several processes of interview and observation with some selected informants. The research study revealed that different people from different background would receive online media as their health educator from different levels. From this research study, the researchers concluded that the three informants receive online media as their primary health educator. However, because of their educational, motivational, social and technological access, they performed different approach of receiving online media as their health educator.